MLN4924 suppresses tumor metabolism and growth of clear cell renal cell carcinoma by stabilizing nuclear FBP1 - Yajing Yang; Yan Ma; Shiyin Fan; Jie Zhu; Bin Ye; Ruonan Zhang; Jiaxi Li; Hongchen Li; Zhencang Zheng; Yufeng Li; Lei Lv (Cell Death Discovery)
Abstract Fructose-1, 6-bisphosphatase (FBP1) is a tumor suppressor and frequently deficient in various cancers, including clear cell renal cell carcinoma (ccRCC). VHL inactivation mutations are usually observed in ccRCC, which can lead to abnormal activation of the HIF signaling pathway. FBP1 could enter the nucleus and restrain HIF function in a non-enzymatic manner. However, its regulatory mechanism in ccRCC tumorigenesis remains poorly understood. Here, we report that nuclear FBP1 is degraded through the ubiquitin-proteasome pathway, and CUL4B acts as Cullin-RING E3 ubiquitin ligase (CRL) to promote the degradation of FBP1 in nucleus, while the neddylation inhibitor MLN4924 could inactivate CUL4B E3 ligase, block proteasomal degradation of FBP1 and suppress HIF target gene expression, including GLUT1, LDHA, PDK1 and VEGF, leading to decreased glucose uptake and lactate and NADPH production, thereby repressing tumor growth of ccRCC. Furthermore, MLN4924 sensitizes ccRCC to γ-glutamylcysteine synthetase inhibitor Buthionine sulfoximine (BSO) treatment in vivo. Collectively, these findings proposed that MLN4924 could inhibit the tumor growth of VHL deficiency-driven ccRCC by stabilizing FBP1, providing new target and strategy for clinic treatment of ccRCC.